In Situ Synthesis of Robust Conductive Cellulose/Polypyrrole Composite Aerogels and Their Potential Application in Nerve Regeneration1. Issue 21 (7th April 2014) - Shi, Zhuqun; Gao, Huichang; Feng, Jiao; Ding, Beibei; Cao, Xiaodong; Kuga, Shigenori; Wang, Yingjun; Zhang, Lina; Cai, Jie
Abstract Nanostructured conductive polymers can offer analogous environments for extracellular matrix and induce cellular responses by electric stimulation, however, such materials often lack mechanical strength and tend to collapse under small stresses. We prepared electrically conductive nanoporous materials by coating nanoporous cellulose gels (NCG) with polypyrrole (PPy) nanoparticles, which were synthesized in situ from pyrrole monomers supplied as vapor. The resulting NCG/PPy composite hydrogels were converted to aerogels by drying with supercritical CO2, giving a density of 0.41–0.53 g cm−3, nitrogen adsorption surface areas of 264–303 m2 g−1, and high mechanical strength. The NCG/PPy composite hydrogels exhibited an electrical conductivity of up to 0.08 S cm−1. In vitro studies showed that the incorporation of PPy into an NCG enhances the adhesion and proliferation of PC12 cells. Electrical stimulation demonstrated that PC12 cells attached and extended longer neurites when cultured on NCG/PPy composite gels with DBSA dopant. These materials are promising candidates for applications in nerve regeneration, carbon capture, catalyst supports, and many others.